2020
DOI: 10.1371/journal.pone.0231082
|View full text |Cite
|
Sign up to set email alerts
|

Sediment drying-rewetting cycles enhance greenhouse gas emissions, nutrient and trace element release, and promote water cytogenotoxicity

Abstract: OPEN ACCESS Citation: Paranaíba JR, Quadra G, Josué IIP, Almeida RM, Mendonça R, Cardoso SJ, et al. (2020) Sediment drying-rewetting cycles enhance greenhouse gas emissions, nutrient and trace element release, and promote water cytogenotoxicity. PLoS ONE 15(4): e0231082.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(7 citation statements)
references
References 84 publications
1
6
0
Order By: Relevance
“…According to our results, the input of this fresh terrestrial organic matter might affect these aquatic ecosystem's role to regional and global carbon cycle, perhaps increasing CO 2 evasion in the first moment (as recently demonstrated by Pinheiro et al 2021) but leading to CO 2 sinks due to N and P accumulation in a longer time scale (Tonetta et al, 2018). However, studies have shown that rewetting sediments previously exposed to direct contact with the atmosphere boosts carbon emissions (especially CO 2 ) (Kosten et al, 2018;Paranaı ´ba et al, 2020), in addition to releasing large amounts of nutrients (N and P) and trace elements (Iron, Manganese and Zinc) to the water column. This shift in the metabolic conditions may explain the very unstable CO 2 balance in semiarid eutrophic reservoirs as recently recorded (Mendonc ¸a Jr.…”
Section: Discussionsupporting
confidence: 65%
“…According to our results, the input of this fresh terrestrial organic matter might affect these aquatic ecosystem's role to regional and global carbon cycle, perhaps increasing CO 2 evasion in the first moment (as recently demonstrated by Pinheiro et al 2021) but leading to CO 2 sinks due to N and P accumulation in a longer time scale (Tonetta et al, 2018). However, studies have shown that rewetting sediments previously exposed to direct contact with the atmosphere boosts carbon emissions (especially CO 2 ) (Kosten et al, 2018;Paranaı ´ba et al, 2020), in addition to releasing large amounts of nutrients (N and P) and trace elements (Iron, Manganese and Zinc) to the water column. This shift in the metabolic conditions may explain the very unstable CO 2 balance in semiarid eutrophic reservoirs as recently recorded (Mendonc ¸a Jr.…”
Section: Discussionsupporting
confidence: 65%
“…Taking into account all sampling points, CO 2 emissions from El Gergal drawdown areas were negatively related to the distance to the shore (r = -0.18; p < 0.05, Fig. 3a), revealing that recently exposed sediments sustain higher CO 2 emission (Jin et al, 2016;Paranaíba et al, 2020), and pointing out the role of rapid hydrological changes on CO 2 evasion from drawdown. Exposed sediments particle size also depicted a negative relation with CO 2 emission, with significant higher CO 2 efflux in fine sand areas than in coarse sand zones, while there were no CO 2 emissions from the larger particle's patches (see Fig.…”
Section: Resultsmentioning
confidence: 98%
“…In agreement, we found a positive and significant relationship between exposed sediment temperature and distance to the shoreline (r = 0.24; p < 0.001), so warmer exposed sediments were also probably the drier, and some water content is essential as a transport medium for nutrients required by microbial communities. Accordingly, Paranaíba et al (2020) found peaks in CO 2 emissions when exposed reservoir sediments transitioned from wet to dry, with fluxes declining as sediments dry out.…”
Section: Resultsmentioning
confidence: 98%
“…Consequently, there is a rationale for allowing marginal trees to develop, providing shade to mitigate against extreme heat and the potential for such disbenefits to occur (Kail et al, 2021). Trees may also help to mitigate the potential disbenefit of enhanced greenhouse gas emissions from temporary ponds, which have been observed as a result of sediment drying–rewetting cycles (Obrador et al, 2018; Paranaíba et al, 2020). Our results indicate that features are significant sinks for POC, however the extent to which this carbon remains in situ is not yet fully understood.…”
Section: Discussionmentioning
confidence: 99%